PERAKITAN 3D PRINTER FUSED DEPOSITE MODELING (FDM) BERBASIS ARDUINO MEGA 2560 - Putra, Alpin Kurnia; Fidiyanto, Faqih; Prakoso, Bayu; Armantya, Rian Zandy; Al Haris, Firdhaus Hari Saputro (JURNAL GAUNG INFORMATIKA, 2019)
3D Printer is a hardware used to print object in 3D. The objects are designed in Computer Aided Design (CAD) software. The purpose of building 3D Printer using arduino mega 2560 is to reduce the production cost. So, the micro small and medium enterprises will have chances to prototype their own product. This research was using experimental method to built the 3D Printer. There are four main steps on building the 3D Printer : (1) Framing, (2) Building the extruder, (3) Configuring the code, and (4) Powering the printer. This research was taken on April to October 2018, in Surakarta and Yogyakarta. The result of this research is a 3D Printer based on Arduino Mega which can print object up to 0.4mm detail and cost less than IDR 2.4 Million, which mean it?s the cheapest 3D Printer with 30cm x 30cm working area.